Sexual Domestic Violence Impact upon Reproductive Health during COVID-19 Pandemic among Women at Baghdad City - Zahraa B. Ahmed; Iqbal M. Abass (Kufa Journal for Nursing Sciences)
Background: Sexual violence is widespread, affects women of all cultures globally, breeds in silence, and finds legitimacy through cultural norms. Proprietors are partners, husbands, family, and friends. It may be domestic violence (DV), sexual (SV), a serious violation of women’s rights as human beings. It is an important cause of physical, psychological and sexual reproductive health problems.